2022
DOI: 10.3390/su14042400
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Village Carbon Footprint after COVID-19 Pandemic: A Challenge to Sustainability

Abstract: The tourism industry is the most significant global Green House Gases (GHGs) contributor, which is often specifically produced by exploratory activities. This leads to the performance of several actions to reduce carbon emissions and maintain sustainable development. Since the Indonesian Tourism Village is a “carbon emission contributor and COVID-19 pandemic impact victim”, the low-carbon exploration should be necessarily implemented to achieve sustainability. Therefore, this study aims to determine the carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The results of the adjusted model showed that there was no statistically significant difference between the times before and during the pandemic, i.e., p < 0.05. A similar result also occurred in the study carried out in Indonesia on the reduction in tourists on the islands; despite the reduction in visitors, there was no significant reduction in CO 2 emission in the region [56].…”
Section: Ecological Footprint Before and During The Covid-19 Pandemicsupporting
confidence: 78%
“…The results of the adjusted model showed that there was no statistically significant difference between the times before and during the pandemic, i.e., p < 0.05. A similar result also occurred in the study carried out in Indonesia on the reduction in tourists on the islands; despite the reduction in visitors, there was no significant reduction in CO 2 emission in the region [56].…”
Section: Ecological Footprint Before and During The Covid-19 Pandemicsupporting
confidence: 78%
“…Tourism's impact on society is generally positive. Rational tourism consumption can achieve two international goals of gender equality [15] and poverty reduction [16,17]. However, the role of tourism in poverty eradication is limited and may only occur in the developing countries [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pandemic affected the arrival of travelers, which declined by seventy four percent, approximately 1 billion trips, within January-December 2020 [21,22]. In 2018, Europe ranked first globally in global arrivals, with 713 million, over 1/2 of the worldwide quantity, showing an annual increase of 6% [23,24].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%